Degrading traumatic memories with eye movements: a pilot functional MRI study in PTSD. Issue 1 (1st December 2016) - Thomaes, Kathleen; Engelhard, Iris M.; Sijbrandij, Marit; Cath, Danielle C.; Van den Heuvel, Odile A.
Abstract : Background: Eye movement desensitization and reprocessing (EMDR) is an effective treatment for posttraumatic stress disorder (PTSD). During EMDR, the patient recalls traumatic memories while making eye movements (EMs). Making EMs during recall is associated with decreased vividness and emotionality of traumatic memories, but the underlying mechanism has been unclear. Recent studies support a "working-memory" (WM) theory, which states that the two tasks (recall and EMs) compete for limited capacity of WM resources. However, prior research has mainly relied on self-report measures. Methods: Using functional magnetic resonance imaging, we tested whether "recall with EMs, " relative to a "recall-only" control condition, was associated with reduced activity of primary visual and emotional processing brain regions, associated with vividness and emotionality respectively, and increased activity of the dorsolateral prefrontal cortex (DLPFC), associated with working memory. We used a randomized, controlled, crossover experimental design in eight adult patients with a primary diagnosis of PTSD. A script-driven imagery (SDI) procedure was used to measure responsiveness to an audio-script depicting the participant's traumatic memory before and after conditions. Results: SDI activated mainly emotional processing-related brain regions (anterior insula, rostral anterior cingulate cortex (ACC), and dorsomedial prefrontal cortex), WM-related (DLPFC), and visual (association) brain regions before both conditions. Although predicted pre- to post-test decrease in amygdala activation after "recall with EMs" was not significant, SDI activated less right amygdala and rostral ACC activity after "recall with EMs" compared to post-"recall-only." Furthermore, functional connectivity from the right amygdala to the rostral ACC was decreased after "recall with EMs" compared with after "recall-only." Conclusions: These preliminary results in a small sample suggest that making EMs during recall, which is part of the regular EMDR treatment protocol, might reduce activity and connectivity in emotional processing-related areas. This study warrants replication in a larger sample. Highlights of the article: Script driven imagery (SDI) before and after recall of traumatic memories is feasible to investigate working mechanisms of degrading of traumatic memories with eye movements (EMs) in PTSD. Right amygdala and rostral ACC activity was significantly lower after "recall with EMs" than after "recall-only". Functional connectivity from amygdala to rostral ACC was decreased after "recall with EMs" vs. "recall-only". This study warrants replication in a larger sample.